Global variations in the definition and management of multifocal and multicentric breast cancer: the MINIM international survey - GÜLLÜOĞLU, MAHMUT BAHADIR (My University, 2022)
The aim of this survey was to understand variation in the definition and management of multifocal and multicentric breast cancer globally. Some 743 physicians from 100 countries responded to this survey, which has provided a clear snapshot of international practice that can inform future work in this area. There is variation in the definition and management of multifocal/multicentric breast cancer among the international breast surgical community, the most controversial aspect being the use of MRI.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Surgery Medicine Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Surgery